Role of Flavonoids in the Treatment of Iron Overload - Wang, Xiaomin; Li, Ye; Han, Li; Li, Jie; Liu, Cun; Sun, Changgang (Frontiers in Cell and Developmental Biology, 2021)
Iron overload, a high risk factor for many diseases, is seen in almost all human chronic and common diseases, including cancer and blood diseases. Iron chelating agents are often used for treatment but, at present, most of these have a narrow scope of application, obvious side effects, and other disadvantages. Recent studies have shown that flavonoids can affect iron status, reduce iron deposition, and inhibit the lipid peroxidation process caused by iron overload. Therefore, flavonoids with iron chelating and antioxidant activities may become potential complementary therapies. In this study, we not only reviewed the research progress of iron overload and the regulation mechanism of flavonoids, but also studied the structural basis and potential molecular and cellular mechanism of their function. In addition, the advantages and disadvantages of flavonoids as plant iron chelating agents are discussed to provide a foundation for the prevention and treatment of iron homeostasis disorders using flavonoids.